Biopsy interpretation of the kidney and adrenal gland - Tickoo, Satish K.; Chen, Ying-Bei; Zynger, Debra L. (Biopsy interpretation series., 2016)
This practical volume in the Biopsy Interpretation Series is your guide to effectively diagnosing surgical pathology specimens from the kidney and adrenal glands, with an emphasis on core needle biopsies. Presented in a reader-friendly format, it features abundant photomicrographs of actual biopsy samples as well as correlative photos of surgical specimens and ancillary immunohistochemical studies. Coverage of each organ includes an introduction to biopsy techniques and an overview of normal histology. Positive diagnoses for renal lesions are described by a pattern approach and tumor type, and adrenal lesions are grouped by primary and metastatic tumors, reflecting the main diagnostic considerations.